Structural changes in socio-affective networks: Multi-modal MRI findings in long-term meditation practitioners. (31st July 2018) - Engen, Haakon G.; Bernhardt, Boris C.; Skottnik, Leon; Ricard, Matthieu; Singer, Tania
Abstract: Our goal was to assess the effects of long-term mental training in socio-affective skills on structural brain networks. We studied a group of long-term meditation practitioners (LTMs) who have focused on cultivating socio-affective skills using loving-kindness and compassion meditation for an average of 40k h, comparing these to meditation-naïve controls. To maximize homogeneity of prior practice, LTMs were included only if they had undergone extensive full-time meditation retreats in the same center. MRI-based cortical thickness analysis revealed increased thickness in the LTM cohort relative to meditation-native controls in fronto-insular cortices. To identify functional networks relevant for the generation of socio-affective states, structural imaging analysis were complemented by fMRI analysis in LTMs, showing amplitude increases during a loving-kindness meditation session relative to non-meditative rest in multiple prefrontal and insular regions bilaterally. Importantly, functional findings partially overlapped with regions of cortical thickness increases in the left ventrolateral prefrontal cortex and anterior insula, suggesting that these regions may play a central role in the generation of emotional states relevant for the meditative practice. Our multi-modal MRI approach revealed structural changes in LTMs who have cultivated loving-kindness and compassion for a significant period of their life in functional networks activated by these practices. These preliminary cross-sectional findings motivate future longitudinal work studying brain plasticity following the regular practice of skills aiming at enhancing human altruism and prosocial motivation. Highlights: Multimodal MRI in long-term meditators (LTMs) and meditation-naïve controls. Cortical thickening in LTMs vs controls in fronto-insular regions. Overlap with fMRI amplitude increases during loving-kindness meditation in LTMs. Findings motivate longitudinal studies addressing training-related plasticity.